Penggunaan Model Pembelajaran Field Trip dalam Meningkatkan Keterampilan Menulis Karangan Deskripsi Bahasa Jerman Siswa - Elfrida Enung; Misnawaty Usman (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2019)
The purpose of this study was to know the effectiveness of Field-Trip-Learning-method in writing a German description essay. This study used quasi-experiment approach. The sample in this study is random sampling. Data is analyzed using t-Test analysis. The result of data analysis shows that t-count 8,44> t-table 2,000 at significant level of 0.05. The results showed that The Field-Trip-Learning method is effectively used in increasing student’s writing skill.